Qualitative study to explore radiologist and radiologic technologist perceptions of outcomes patients experience during imaging in the USA. Issue 7 (20th July 2020) - Zigman Suchsland, Monica; Cruz, Maria Jessica; Hardy, Victoria; Jarvik, Jeffrey; McMillan, Gianna; Brittain, Anne; Thompson, Matthew
Abstract : Objective: We aimed to explore the patient-centred outcomes (PCOs) radiologists and radiologic technologists perceive to be important to patients undergoing imaging procedures. Design: We conducted a qualitative study of individual semi-structured interviews. Participants: We recruited multiple types of radiologists including general, musculoskeletal neuroradiology, body and breast imagers as well as X-ray, ultrasound, CT or MRI radiologic technologists from Washington and Idaho. Outcome: Thematic analysis was conducted to identify themes and subthemes related to PCOs of imaging procedures. Results: Ten radiologists and six radiology technologists participated. Four main domains of PCOs were identified: emotions, physical factors, knowledge and patient burden. In addition to these outcomes, we also identified patient and provider factors that can potentially moderate these outcomes. Conclusions: Radiologists and technologists perceived outcomes related to the effect of imaging procedures on patients' emotions, physical well-being, knowledge and burden from financial and opportunity costs to be important to patients undergoing imaging procedures. There are opportunities for the radiology community to measure and use these PCOs in comparisons of imaging procedures and potentially identify areas where these outcomes can be leveraged to drive a more patient-centred approach to radiology.